Tanggung Jawab Sosial Badan Usaha Milik Negara dalam Menumbuhkan Kemandirian Masyarakat di Sulawesi Selatan - Abdul Rauf (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
State-owned enterprises (SOEs) social responsibility is important to maintain continuity of production to the goal of building the social legitimacy, even the implementation of social responsibility in SOEs has become a liability in accordance with the legislation in force. However, reality shows that the implementation of social responsibility by the state has not been able to play an optimal role in fostering self-reliance. Therefore, the issues to be discussed is how a form of implementation of social responsibility SOEs to foster self-reliance. This research was conducted by examining theories and provisions of relevant laws and connected with the application in the field. The research was conducted on a five (5) SOEs in South Sulawesi as a sample. The results showed that the implementation of social and environmental responsibility by the state is a form of concern on the part of the company on surrounding communities and the environment, which is implemented in the form of the Partnership and Community Development Program coupled with other social programs are referred to as BUMN Peduli. However, in order to foster self-reliance of society, there should be synchronization between the activities of the partnership program with environmental development program. Provide guidance to the public should also be conducted on an ongoing basis from the provision of training, provision of capital, mentoring, until the people who nurtured can be sought independently.